ON THE SEAMLESS INTEGRATION AND CO-EXISTENCE OF CHIPLESS RFID IN BROAD IOT FRAMEWORK - Sharma, Vijay; Hashmi, Mohammad S. (IEEE Access, 2021)
RFID has permeated in wide-ranging applications that may eventually fall under the broad IoT umbrella. However, the adaption of RFID for commercial purposes of IoT-centric applications still faces numerous technical challenges due to its high cost. The Chipless RFID can become a boon considering its significantly reduced cost and tag complexity in this context. In this article, therefore, different aspects of the chipless RFID are discussed and analyzed, and a potential road map is explored for the effective seamless integration of chipless RFID in the amalgamated IoT. At first, a brief theoretical preliminary about the Chipless RFID is presented, and it is succeeded by the application’s specific roles of this emerging RFID in the wide variety of domains. Subsequently, the analysis of various physical parameters shows that chipless RFID technology can greatly broaden IoT’s horizon. It essentially shows that it has the potential to bring a paradigm shift in the way RFID can coexist with IoT. Finally, a section which briefs about the future directions is also included to throw some light on Chipless RFID’s direct fitment in the IoT.
Keywords: Type of access: Open Access; RFID